Bahasa Inggris - Susan Febriantina; Retno Wijayanti (Fakultas Ekonomi Universitas Negeri Jakarta, 2018)
The objective of this research is to get factual data about the readiness of public primary schools in Indonesia based on eight indicators of child-friendly school. By using purposive sampling technique method, the research sample is teachers at public primary school. The descriptive research method was used to analyze the data. The result shows that 84 % of children friendly school policy achievement; b) 75% of health program and facilities achievement c) 67 % of safe, comfortable, and healthy environment and infrastructure) 82% of children’s participation achievement; e) 86% of positive values habituation; f) 67% of well-trained teacher’s availability of child rights convention; g) 39% of student’s route safety; h) and 58% of community and government’s participation.